A retrospective study of factors which determine a negative blood culture in Cambodian children diagnosed with enteric fever. (2nd April 2016) - Bousfield, Rachel; Thyl, Miliya; Samol, Orng; Rithea, Loet; Sona, Soeng; Chhat, Hor Put; Poda, Sar; Moore, Cartin E.; Chheng, Kheng; Kumar, Varun; Day, Nicholas P. J.; Parry, Christopher M.
Abstract : Background: Blood cultures are used to confirm a diagnosis of enteric fever but reported sensitivities can be as low as 40%. Aims: To determine the factors associated with a negative blood culture in Cambodian children with suspected enteric fever. Methods: In a retrospective study of hospitalised Cambodian children given a discharge diagnosis of enteric fever, the following factors associated with a negative blood culture were analysed: age, blood culture volume, prior antibiotic therapy, duration of illness and disease severity. Results: In 227 hospitalised Cambodian children with a discharge diagnosis of enteric fever, it was confirmed in 70% by a positive blood culture. There was no association between a negative blood culture and younger age, lower blood volumes for culture, prior antibiotic therapy, a late presentation or milder disease. Conclusions: Although blood culture sensitivity was higher than expected, alternative simple, rapid and sensitive tests are needed for diagnosing enteric fever.